CIRCULATION OF PRODUCTION AND FRAMING OF ISLAMIC TERRORISM (CASE STUDY OF THREE CHURCH BOMBINGS IN SURABAYA) - Sabiq Muhammad; Imam Nawawi; Arisnawawi (FAKULTAS DAKWAH UIN SALATIGA, 2023)
Islamic radicalism and terrorism are social facts, and continue to metamorphose until they become digital facts. The transition from physical space to digital space does not change the status of radicalism and terrorism as social facts but changes its character to become a digital social fact. Character changes are accompanied by narrative shifts, where the framing by the media is often more solid than before the transition. The solidity of the media's framing of Islamic radicalism and terrorism creates a distinct digital social structure, which consists of producers, production stages, and ongoing reproduction of issues. This research argues that narrative shifts due to media framing are supported by corporate interests, media political affiliations, and the ideology promoted. Scheufele and Tewksbury explained narrative shifts due to media framing, and the agenda behind media framing was analyzed based on McCombs' theory. This research concludes that the narrative shift due to framing by the media was carried out deliberately because of corporate interests, political affiliations, and the ideology of the media owners. During the production of framed information, civil control over framing media is not optimal.